Woman…you know what you are - Jiménez Carbajal, Alicia Ruth (2020)
From the sexed nature of human beings, much has been said about the dominance of one sex over the other. Faced with this, the terms patriarchy and matriarchy arise not necessarily in that order, such as force, dominance or control over the other.The historical evidence recognizes the actions of women in public positions within prehistoric society to the point of using the term matriarchy, which fades in the Neolithic with the consolidation of sedentary life, and in the nascent social organization it is the male who exercises authority as head of the family, giving rise to the patriarchy.It is in the nineteenth century that the first feminist movements were born to later take up the debate on patriarchy whose theorization, from different perspectives, has given rise to different currents of feminism, each with a particular vision of female identity.